Rereading the Ark Narrative: An Exilic Word of Hope and Warning - Beach, Matthew D. (Horizons in biblical theology, 2018)
This article explains how 2 Sam 6:1-8 was redacted during the Babylonian exile in order to impart a theological message of hope and warning to the exilic community. This is demonstrated through an exploration of the similarities between 2 Sam 6:1-8 and Exod 32. The primary similarities include: (1) how Uzzah fulfills the same priestly role as Aaron; (2) how David serves as a symbolic “Moses figure” who guides the people and the ark to Jerusalem; and (3) how Yahweh broke out against Uzzah in anger, symbolic of how Yahweh allowed the Babylonian army to overthrow Jerusalem and take the people captive.